Understanding mobile use behavior, stigma and associated needs among female sex workers in Nepal: a qualitative study - Ranjit, Yerina S.; Meisenbach, Rebecca; Roscoe, Rikki; Joshi, Omita (Frontiers in Communication, 2024)
Female sex workers (FSWs) in Nepal continue to disproportionately experience increased HIV risk alongside individual, social, and structural barriers to accessing and using health services. Innovative methods are needed to provide improved HIV prevention information and other health services for FSWs. Mobile health (mHealth) is a mechanism that can overcome structural and social barriers. Studies show that FSWs are increasingly using mobile phones to solicit clients. Hence, this exploratory study using the Uses and Gratifications (U&G) framework aimed to understand Nepali FSWs' mobile use behavior, including the purposes they use it for. We conducted four focus group discussions. Results showed that FSWs in Nepal used mobile phones to gratify their needs to: 1) manage their profession, 2) maintain social connection, 3) to keep their sex work information hidden 4) have access to information in a stigma-free environment. The study's findings can be instrumental in developing and designing innovative health interventions to reduce HIV and STI incidents in this population.